2012
DOI: 10.1186/1747-597x-7-2
|View full text |Cite
|
Sign up to set email alerts
|

The social production of substance abuse and HIV/HCV risk: an exploratory study of opioid-using immigrants from the former Soviet Union living in New York City

Abstract: BackgroundSeveral former Soviet countries have witnessed the rapid emergence of major epidemics of injection drug use (IDU) and associated HIV/HCV, suggesting that immigrants from the former Soviet Union (FSU) may be at heightened risk for similar problems. This exploratory study examines substance use patterns among the understudied population of opioid-using FSU immigrants in the U.S., as well as social contextual factors that may increase these immigrants' susceptibility to opioid abuse and HIV/HCV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 40 publications
(57 reference statements)
2
48
0
Order By: Relevance
“…The stigma faced by lesbian/bisexual SWs may result in internalized homophobia, which has been suggested as a possible explanation of increased rates of substance use among lesbian and bisexual women (Rosario, Schrimshaw, & Hunter, 2008; Young, Friedman, & Case, 2005). Finally, research suggests that social networks may play an important role in HIV risk pathways (Guarino, Moore, Marsch, & Florio, 2012; Rhodes, Singer, Bourgois, Friedman, & Strathdee, 2005), and it is possible that lesbian/bisexual SWs work in specific social networks where there is overlap between non-injection stimulant use and sex work.…”
Section: Discussionmentioning
confidence: 99%
“…The stigma faced by lesbian/bisexual SWs may result in internalized homophobia, which has been suggested as a possible explanation of increased rates of substance use among lesbian and bisexual women (Rosario, Schrimshaw, & Hunter, 2008; Young, Friedman, & Case, 2005). Finally, research suggests that social networks may play an important role in HIV risk pathways (Guarino, Moore, Marsch, & Florio, 2012; Rhodes, Singer, Bourgois, Friedman, & Strathdee, 2005), and it is possible that lesbian/bisexual SWs work in specific social networks where there is overlap between non-injection stimulant use and sex work.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research documents similar patterns among injecting PO misusers (Surratt, Kurtz and Cicero, 2011; Lankenau et al, 2012; Johnson et al, 2013). Behaviors such as sharing syringes and other drug-injection equipment, use of shooting galleries and communal sharing of drug solution in group-injection situations have been well-documented among young heroin injection initiates and may place them at high risk for HIV and/or HCV transmission (Fuller et al, 2003; Goldsamt, Harocopos, Kobrak, Jost & Clatts, 2010; Harocopos, Goldsamt, Kobrak, Jost & Clatts, 2009; Guarino, Moore, Marsch & Florio, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these studies are limited in generalizability inasmuch as they use samples of youth from particular national/ethnic groups or specifi c regions of the United States (Turner and Gil, 2002). Investigations from adult samples focused on emigrants from Mexico (Borges et al, 2009(Borges et al, , 2012, the former Soviet Union (Guarino et al, 2012), Asia (Moloney et al, 2008;Wong et al, 2007), and Latin America (Alegría et al, 2008;Ojeda et al, 2008) have found trends similar to those identifi ed in younger samples. Studies of adults in the United States have been hampered by their inability to examine the stability of the relationship between substance use and immigration across multiple immigrant generations or among emigrants from various regions of the world (Johnson et al, 2002;Li and Wen, 2013;Salas-Wright and Vaughn, 2014).…”
mentioning
confidence: 97%